Usefulness of dorsal laser evoked potentials in patients with spinal cord damage: report of two cases. Issue 6 (1st December 2001) - Iannetti, GD; Truini, A; Galeotti, F; Romaniello, A; Manfredi, M; Cruccu, G
Abstract : Stimulation of the dorsal skin with brief laser impulses easily evokes brain potentials (laser evoked potentials, LEPs). Dorsal LEPs were first used to study the conduction velocity in the human spinothalamic tract. In this study the diagnostic usefulness of this technique was assessed by recording dorsal LEPs in two patients with focal spinal cord lesions (one intrinsic and the other extrinsic) and spared lemniscal sensitivities. In both cases, the brain evoked potentials were normal after stimulation of the metamers above the lesion but absent after stimulation of those below. Dorsal LEP recordings may prove a useful tool in localising lesions and in the neurophysiological assessment of focal spinal cord lesions involving the anterolateral quadrants of the spinal cord.